Potential Neurotoxic Effects of Glioblastoma-Derived Exosomes in Primary Cultures of Cerebellar Neurons via Oxidant Stress and Glutathione Depletion - Sidika Genc; Manuela Pennisi; Yesim Yeni; Serkan Yildirim; Giuseppe Gattuso; Meric A. Altinoz; Ali Taghizadehghalehjoughi; Ismail Bolat; Aristidis Tsatsakis; Ahmet Hacımüftüoğlu; Luca Falzone (MDPI AG, 2022)
High-grade gliomas are the most fatal brain tumors. Grade 4 gliomas are called glioblastoma multiforme (GBM), which are associated with the poorest survival and a 5-year survival rate of less than 4%. Many patients with GBM developed concomitant cognitive dysfunctions and epilepsy. Although the cognitive decline is well defined in glioblastomas, the neurotoxic factors underlying this pathology are not well understood in GBM patients. In this study, we aimed to investigate whether GBM-derived exosomes play a role in neuronal toxicity. For this purpose, exosomes obtained from T98G and U373 GBM cells were applied to primary neuron culture at different concentrations. Subsequently, MTT, LDH, GSH, TAS, and TOS tests were performed. Both GBM-derived exosomes induced a dose-dependent and statistically significant increase of LDH release in cerebellar neurons. MTT assay revealed as both T98G and U373 GBM-derived exosomes induced dose-dependent neurotoxic effects in cerebellar neurons. To the best of our knowledge, this study is the first study demonstrating the toxic potential of GBM-derived exosomes to primary neurons, which may explain the peritumoral edema and cognitive decline in GBM patients.